Fast-evolving homeobox genes in mammalian preimplantation development - Lewin, TD (2023)
Transcription factor proteins containing the homeodomain motif orchestrate myriad key functions during embryonic development and are therefore often conserved to a spectacular degree over extensive evolutionary timescales. Given this paradigm, the recent discovery of several homeobox families with roles in embryogenesis but which appear to be rapidly-evolving is a puzzling development. In this thesis I focus on one such group, the mammalian-specific Eutherian Totipotent Cell Homeobox (ETCHbox) genes, with the overarching aim of advancing our understanding of the function fast- evolving genes perform in the embryo and the forces that have combined to produce their unusual evolutionary trajectories. Analysis of single-cell RNA-sequencing data finds that ETCHbox genes are activated during the major wave of embryonic genome activation across various mammalian species. Ectopic expression experiments of ETCHbox proteins in cell culture suggest them to be multifunctional regulators of several key processes during preimplantation development, including blastocyst formation; inner cell mass development; the activity of transposable elements; and cellular potency. From an evolutionary perspective, dramatic changes in ETCHbox protein-coding sequences and copy number have occurred between lineages, and this has been driven at least in part by positive selection. Rapid protein-coding sequence evolution has resulted in small alterations to gene functions between closely related species (e.g. within primates) but highly divergent transcription factor functions between humans and cattle. Overall, I conclude that the lability of preimplantation development, combined with functional redundancy of ETCHbox proteins and positive selection acting on ETCHbox sequences, have combined to produce the diverse repertoires we observe today.